Experiments and modeling on FTU tokamak for EC assisted plasma start-up studies in ITER-like configuration. (17th August 2015) - Granucci, G.; Garavaglia, S.; Ricci, D.; Artaserse, G.; Belli, F.; Bin, W.; Calabrò, G.; Cavinato, M.; Farina, D.; Figini, L.; Moro, A.; Ramogida, G.; et al.
Abstract: The intrinsic limited toroidal electric field (0.3 V m −1 ) in devices with superconducting poloidal coils (ITER, JT-60SA) requires additional heating, like electron cyclotron (EC) waves, to initiate plasma and to sustain it during the burn-through phase. The FTU tokamak has contributed to studying the perspective of EC assisted plasma breakdown. Afterward, a new experimental and modeling activity addressing the study of assisted plasma start-up in a configuration close to the ITER one (magnetic field, oblique injection, and polarization) has been performed and is presented here. These experiments have been supported by a 0D code, BKD0, developed to model the plasma start-up and linked to a beam tracing code computing, in a consistent way, EC absorption. The FTU results demonstrate the role of polarization conversion at the inner wall reflection. Dedicated experiments also showed the capability of EC power to sustain plasma start-up in the presence of strong error field (12 mT), with a null outside the vacuum vessel. The BKD0 code, applied to FTU data, has been used to determine the operational window of sustained breakdown as a function of toroidal electric field and neutral pressure. Experimental results in agreement with the BKD0 simulations support the use of the code to predict start-up in future tokamaks, like ITER and JT60SA.